PENCARIAN KESAKSIAN KRISTEN YANG RELEVAN DI ASIA (Kosuke Koyama: Injil Menurut Pandangan Asia) - Eben Nuban Timo (Institut Filsafat dan Teknologi Kreatif Ledalero, 2013)
To live as church in Asia is very demanding. Asia is known as the continent that gave birth to world religions whose followers in Asia live close to one another as neighbours. Each religion has a certain knowledge about the spiritual richness of her neighbours. Buddhists, for example, know that Christians are requested by the Lord to live a life of self-sacrifice. Christians are called by their master (Jesus) not to go forward fighting on behalf of the cross but to bear their cross on behalf of Jesus, not displaying a self-glorified life but practising self-denial. How is this command to be fulfilled in Asia by the Christian Church? This essay discusses the perspective of one of Asia’s most prominent theologians, Kosuke Koyama. Kata-kata Kunci: Teologi Asia, Tafsiran Dunia Ketiga, Kristologi Asia, Dialog antar Iman dan Agama-agama Asia.